Pengaruh Kerawanan Pangan, Bantuan Pangan dan Jaminan Kesehatan terhadap Keluhan Kesehatan - Sari, Ofi Ana; Nachrowi, Nachrowi Djalal (Jurnal Ekonomi dan Pembangunan Indonesia, 2022)
The health condition of the Indonesian from life expectancy at birth tends to increase, but not all years are in a healthy. The health conditions can be influenced by food insecurity, food aid and health insurance. This study aims to study the effects of food insecurity, food assistance and health insurance on health complaints. Indonesian Socio-Economic Survey (Susenas) data were analyzed using multinomial logistic regression. The results show that food insecure individu are risky health complaints and are disrupted more than twice than food secure individu. BPJS PBI has a lower risk of health complaints than for paid BPJS. Food assistant and BPJS PBI/Jamkesda reducing probability of health complaints. Government’s intervention focusing on food insecure individu, elderly, and living in rural areas.